THE RAPE OF EUROPA: A COMPARISON BETWEEN OVID AND TITIAN - Thamos, Márcio (Laboratório Editorial FCL-UNESP, 2012)
In Metamorphoses, the Roman poet Ovid tells the tale of the transformation of Jupiter into a bull to seduce the Phoenician princess Europa. During   Renaissance, as is well known, Western civilization fostered an intense renewal of its values under the clear influence of Greco-Roman culture. Ovid, whose fame had not ceased throughout the Middle Ages, became then even better known, and especially his poem Metamorphoses turned into a remarkable source of inspiration not only to literature but also to fine arts and their new humanistic conception. Thus, the episode of the abduction of Europa received a dramatic pictorial expression in the broad brush strokes of the Venetian master Titian Vecellio, who interpreted several classical myths in his canvases at the height of his creative maturity. There are many and obvious relationships in the verses of the ancient Latin poet and the picture of the Italian Renaissancist. In Metamorphoses, the mythical account is described in so many details and set in such an expressive poetic that Titian could take Ovid´s narrative as a model for painting “The Rape of Europa”, doing a true exercise in intersemiotic translation by interpreting verbal signs through pictorial signs.